Biomechanical determination of the relationship between femoral neck lesion size and the risk of pathological fracture - EROL, BÜLENT; TOPKAR, OSMAN MERT (SAGE PUBLICATIONS LTD, 2016)
Purpose: Half of the pathological fractures of the proximal femur occur in the neck region. We evaluate the relationship between the defect size within the femoral neck and the risk of pathological fracture. Methods: After creating metastasis-like lesions in the neck regions of 21 human cadaver femurs, compression was applied to simulate single-limp stance type loading. First, a loading of 600 Newtons (N) was applied to the 35%-defected femoral necks. If the bone fracture did not occur, the defect size was increased to 45% and the 600 N force was applied again. If no fracture was observed then the defect size was increased to 55% and the bones were loaded again. The 55%-defected bones with no fractures were loaded until a fracture was detected. Results: There were no fractures with the 35%- and 45%-defected femurs until 600 N was applied. However, when the defect size was increased to 55%, 3 bones were fractured before reaching 600 N. The fractures occurred at an average of 455 N in the 3 bones. At a compression of 600 N, 18 bones (84%) were intact, and the loading was continued. 18 femurs with 55%-defected neck regions had an average endurance of 1270 N compression (range 750-2800 N). Conclusions: This study showed that even very osteoporotic bones with large metastases can withstand high forces of compressive loading.
Keywords: Bone strength prediction; Femur neck metastases; Pathological fracture; Stance type loading (static balance); METASTATIC LESIONS; STRENGTH; PREDICTION; MANAGEMENT